A single-chamber microbial fuel cell for rapid determination of biochemical oxygen demand using low-cost activated carbon as cathode catalyst. Issue 24 (17th December 2018) - Wang, Ying; Liu, Xianhua; Wang, Meiyu; Zhang, Pingping; Zong, Yanping; Zhang, Qiufeng
ABSTRACT: The biochemical oxygen demand (BOD) is widely used for the evaluation of water and wastewater quality. However, the conventional method to measure BOD is time-consuming and requires complicated processes. In this study, a Microbial fuel cell (MFC)-based BOD sensor was developed by using low-cost activated carbon as the cathode catalyst. The sensor was calibrated with an aerated nutrient medium containing sodium acetate as the BOD source. When the sensor was operated with an external resistance of 1 K Ω, linear correlation ( R 2  = 0.9965) was obtained for BOD concentrations ranging from 80 to 1280 mg/L in a reaction time of 50 h. Besides acetate, glucose/glutamic acid (GGA) and ethanol could also be analyzed by the sensor. In a low concentration range (200 mg/L), the relationship between GGA solution concentration and output voltage was in accord with Monod growth kinetics.